Visualizing Localized Reentry With Ultra–High Density Mapping in Iatrogenic Atrial Tachycardia: Beware Pseudo-Reentry. (April 2017) - Luther, Vishal; Sikkel, Markus; Bennett, Nathan; Guerrero, Fernando; Leong, Kevin; Qureshi, Norman; Ng, Fu Siong; Hayat, Sajad A.; Sohaib, S.M. Afzal; Malcolme-Lawes, Louisa; Lim, Elaine; Wright, Ian; et al.
Abstract : Background—: The activation pattern of localized reentry (LR) in atrial tachycardia remains incompletely understood. We used the ultra–high density Rhythmia mapping system to study activation patterns in LR. Methods and Results—: LR was suggested by small rotatory activations (carousels) containing the full spectrum of the color-coded map. Twenty-three left-sided atrial tachycardias were mapped in 15 patients (age: 64±11 years). 16 253±9192 points were displayed per map, collected over 26±14 minutes. A total of 50 carousels were identified (median 2; quartiles 1–3 per map), although this represented LR in only n=7 out of 50 (14%): here, rotation occurred around a small area of scar (<0.03 mV; 12±6 mm diameter). In LR, electrograms along the carousel encompassed the full tachycardia cycle length, and surrounding activation moved away from the carousel in all directions. Ablating fractionated electrograms (117±18 ms; 44±13% of tachycardia cycle length) within the carousel interrupted the tachycardia in every LR case. All remaining carousels were pseudo-reentrant (n=43/50 [86%]) occurring in areas of wavefront collision (n=21; median 0.5; quartiles 0–2 per map) or as artifact because of annotation of noise or interpolation in areas of incomplete mapping (n=22; median 1, quartiles 0–2 per map). Pseudo-reentrant carousels were incorrectly ablated in 5 cases having been misinterpreted as LR. Conclusions—: The activation pattern of LR is of small stable rotational activations (carousels), and this drove 30% (7/23) of our postablation atrial tachycardias. However, this appearance is most often pseudo-reentrant and must be differentiated by interpretation of electrograms in the candidate circuit and activation in the wider surrounding region. Abstract : Supplemental Digital Content is available in the text.